1980
DOI: 10.1128/aac.17.2.188
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics of Ceforanide (BL-S786R) and Cefazolin in Laboratory Animals and Humans

Abstract: Ceforanide (BL-S786R) is a new, broad-spectrum, parenteral cephalosporin. Pharmacokinetic properties weredetermined in rats (100 mg/kg), rabbits (30 mg/ kg), dogs (25 mg/kg), and humans (2 g or 30 mg/kg) and compared with equivalent single doses of cefazolin. Plasma half-lives for ceforanide and cefazolin were 1.1 and 0.5 h in the rat, 5 and 0.3 h in the rabbit, 1 and 0.8 h in the dog, and 2.6 and 2 h in humans, respectively. The slower elimination of ceforanide, as reflected by longer plasma half-life, larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
1

Year Published

1982
1982
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 9 publications
1
26
1
Order By: Relevance
“…Cefazolin binds to serum proteins to a different extent in dogs and humans. In humans, cefazolin is highly protein bound, with reports ranging from 73 to 92% (9,10,12,13,22,24,30,31), whereas in dogs reports have varied from 32.5% (20) to 47% (13) to 80% (37). The results of this study indicate that serum protein binding of cefazolin in dogs is relatively low, 35.8% by isotope assay and 38.8% by bioassay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cefazolin binds to serum proteins to a different extent in dogs and humans. In humans, cefazolin is highly protein bound, with reports ranging from 73 to 92% (9,10,12,13,22,24,30,31), whereas in dogs reports have varied from 32.5% (20) to 47% (13) to 80% (37). The results of this study indicate that serum protein binding of cefazolin in dogs is relatively low, 35.8% by isotope assay and 38.8% by bioassay.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that cefazolin does not bind to the membrane filtration cones (13,31 (15) Cefazolin concentration in the ultrafiltrate and unfiltered serum was analyzed by isotope and bioassay methods. Standards for the bioassay were prepared with phosphate buffer for the ultrafiltrate samples and with pooled dog serum for the serum samples.…”
mentioning
confidence: 99%
“…According to Actor and co-workers (1), the plasma half-lives of SK&F 75073 (cefonicid) were 124 min in mice, 38 min in dogs, and 97 min in squirrel monkeys. Lee and co-workers (7) reported that the plasma half-lives of ceforanide were 1.1 h in rats, 5.0 h in rabbits, and 1.0 h in dogs. The tl/2(0) values of YM09330, presented by Komiya and colleagues (5), were 13.0 min in mice, 15.9 min in rats, 30.5 min in rabbits, 55.5 min in dogs, and 75.6 min in rhesus monkeys.…”
Section: Methodsmentioning
confidence: 99%
“…The half-life (tQ12) of the drug (2.6 to 2.98 h) in adults is substantially longer than those of most other cephalosporins (4,6). Also, the peak serum concentrations are generally higher, and the areas under the curve (AUCs) are generally larger than the values for other cephalosporins.…”
mentioning
confidence: 93%
“…Initially, only patients older than 1 year were enrolled, but when the safety and efficacy of the drug were established, infants were also included. The age range of the 46 patients (36 males and 10 females) was 1 month to 17 years (mean 5.8 years, median 4 years), and the weight range was 5.2 to 100 kg. All patients had normal blood urea nitrogen and serum creatinine levels.…”
mentioning
confidence: 99%